Development of smart city community service integrated management platform - Lei Qi; Jing Guo (International Journal of Distributed Sensor Networks)
With the acceleration of the construction of smart city in China, the construction of a smart community that acts as the last mile of a smart city is highly valued. Development of smart community service integrated management platform is to utilize intelligent equipment and software platform, to build an information platform for information sharing, service integration, and resource optimization, and to ultimately realize intelligent management and innovative services within the community. In this article, we propose the overall framework and application system of the intelligent community integrated service platform, providing a strong theoretical basis for the construction of smart communities at this stage, and carry out detailed analysis and design of the underlying infrastructure, supporting platform and basic database of the platform.